(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Nanomedicine, a novel concept, bears much hope in delivering drug candidates having low solubility and bioavailability. Nano-emulgel, one of the emerging tools, is considered as ideal carriers for the topical delivery of lipophilic drugs to overcome these challenges in the management of psoriasis and related skin problems. Psoriasis is an auto-immune and chronic inflammatory disease affecting 2-3% population of the world. Current available treatment of psoriasis has limitations such as systemic side effects and low percutaneous permeation, which evokes a dire need to develop an alternative lipoidal nanocarrier system. Nano-emulgel is basically formed by admixing nanoemulsion system with a hydrogel matrix using both high and low energy methods. Various literatures have been reported for lipoidal nanocarriers in topical treatment suggesting reduced dose, improved percutaneous absorption and better bioavailability of lipophilic drugs with nano-emulgel delivery via topical route. Several approved marketed preparations are available that strongly support the stability of these nanocarriers in respect to its efficacy and safety. This supports the fact of using topical nano-emulgel system to deliver lipophilic drugs to overcome the sufferings from oral delivery and improved patient compliance. Therefore, it is suggested as a potential system that can be used for an effective management of psoriasis via topical route in near future. Dhaka Univ. J. Pharm. Sci. 20(2): 235-246, 2021 (December)